Scientific, inquiry, and animation integration: The IPSIA learning model in chemistry - Siregar, Rabiyatul Adawiyah; Ndruru, Sun Theo Constan Lotebulo; Lubis, Armansyah; Siregar, Ali Akbar; Siregar, Nurhijriyah Kam (Jurnal Pendidikan Kimia, 2024)
This study addresses the issue of low active participation among students in chemistry learning, as well as their difficulties in understanding macroscopic, microscopic, and symbolic concepts, which contribute to unsatisfactory learning outcomes. To tackle these challenges and enhance students' performance in chemistry, a valid, practical, and effective IPSIA learning model was developed. The research employed a development approach based on the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model, beginning with a thorough analysis of the curriculum. This was followed by the design of the IPSIA model, which was validated using a questionnaire instrument. The results of the validity test scored 98, categorizing it as "very good." Additionally, the practical test of the IPSIA model also received a score of 98, indicating that it is user-friendly. During the implementation phase, the effectiveness of the model was assessed through test results. The improvement in students' chemistry learning was evidenced by normalized gain scores: 0.57 for the control class and 0.72 for the experimental class at Senior High School (SMA) 2 Padangsidimpuan, as well as 0.52 for the control class and 0.64 for the experimental class at SMA 5 Padangsidimpuan. These findings demonstrate that the IPSIA learning model is valid, practical, and effective in improving students' chemistry learning outcomes.